Analysis of Project Delays on the Work of Abrasion Handling of Panjang Island of Jepara - Eka Yani Astuti (International Conference on Coastal and Delta Areas, 2017)
Ideally, in the construction project, all components of the contract are clearly described to the contractor regarding the agreement, technical specifications, plan drawings, general and special terms, quantity list, implementation plan and schedule to limit the project completion time. However, the cases experienced in the construction are a discrepancy between the plan and the implementation schedule that has been made with the realization in the field, resulting in delays in project completion. The purpose of this study (1) Analyzing the variable factors of labor, work tools, materials, finance, managerial, planning and scheduling of project delays on the work of Panjang Island abrasion handling. (2) Analyze the most dominant variable about project delay of Panjang Island abrasion project. This research method is descriptive quantitative. The research location is in DPUPR of Jepara regency with total sample is 40 respondents. The data analysis is multiple linear regression using SPSS V.21. The results showed that (1) labor, working tools, material, finance, managerial, planning and scheduling variables contributed to the delay in Panjang Island abrasion project. This can be seen from the value of F arithmetic of 136.288 while for the value of F table is 2.34. In addition, the significance value is 0.000. (2) The most dominant variables on the delay of Panjang Island abrasion project are financial, planning and scheduling.   Keywords: Construction Project, Employment, Project Delay